Vapor–Liquid Equilibrium Study of LiBr + H2O and LiBr + CaCl2 + H2O Systems - Wang, Huinan; Chen, Hongfei; Chen, Wanhao; Sun, Haoran; Xu, Xianzhen (Frontiers in Chemistry, 2020)
Vapor–liquid equilibrium (VLE) data and modeling for LiBr + H2O and LiBr + CaCl2 + H2O are reported in this paper. This work focuses on the experimental determination of the boiling point of LiBr + H2O and LiBr + CaCl2 + H2O solutions with vapor pressures between 6 and 101.3 kPa and the total molality of salt ranging from 0 to 21.05 mol•kg−1. The procedures were carried out in a computer-controlled glass apparatus. The relationship between the boiling point and saturated vapor pressure is obtained, and Xu's model is used to correlate and predict the VLE. By correlation of the data (literature and experimental) for LiBr + H2O and LiBr + CaCl2 + H2O, the parameters are obtained. We compared the results with the ElecNRTL model and Pitzer model. The parameters for the LiBr + H2O, CaCl2 + H2O, and LiBr + CaCl2 + H2O systems can be successfully used to calculate and predict the VLE data.